Fatty acid profile of salinity tolerant rice genotypes grown on saline soil - Aziz, A.; Siti Fairuz, M.; Abdullah, M.Z.; Ma, N.L.; Marziah, M. (Penerbit Universiti Kebangsaan Malaysia, 2015)
This paper reports the effect of salinity stress on the fatty acid profile of salinity-tolerant rice grown on saline soil. Three salinity-tolerant rice genotypes obtained from IRRI, namely SS1-40, SS1-41 and SS1-42, were used. The leaves of the control and treatment plants were sampled during the various developmental phases: vegetative, reproductive and ripening. The fatty acid methyl ester (FAME) contents were analysed using gas chromatography techniques. The results revealed that salinity stress significantly influenced the fatty acid content of the three rice genotypes. Palmitic (C16:0), stearic (C18:0), oleic (C18:1), linoleic (C18:2) and linolenic acid (18:3) are the fatty acids that may be involved in the regulation of salinity stress. The levels of these fatty acids were higher in plants that planted under salinity stress than in the control during the vegetative and reproductive stages, but lower during the ripening stage. The finding suggested that salinity stress triggers the biosynthesis of fatty acids, such as linolenic acid, responsible for adaptation and growth development of rice plants in response to salinity stress.